The Effectiveness of Integrated Management Quality (MMT) in JNE Main Branch Gorontalo - Dwi Ayu Hartinah; Abd. Rahman Pakaya; Sri Yulianty Mozin (Journal of International Conference Proceedings (JICP), 2018)
This study aims to describe the effectiveness of Integrated Management Quality (MMT) in JNE Main Branch Gorontalo in terms of (1) socialization program, (2) understanding program, (3) target accuracy, (4) goal achievement, and (5) real change. The method of this research is qualitative with the type of case study research through (i) triangulation of data sources through comparison of the results of interviews with the contents of related documents; (ii) data collection techniques through in-depth interviews with informants and documentation studies; (iii) data analysis techniques through data reduction, data presentation, verification and conclusion. The results of the study are: First, the MMT socialization is carried out less effectively, there were still employees and community customers who had not received complete information about the quality management model implemented in the company. The intensity of the dissemination still needs to be improved through routine breeding to employees and service advertisements for the community. Second, understanding MMT is effective. After getting information about MMT, employees understand about the quality management model implemented in the company. Employees have knowledge of performance quality standards targeted in SOPs. Employees feel easy in following the performance quality standards set by the company. Third, the accuracy of MMT targets is effective. The customer community is satisfied with the effectiveness, efficiency and flexibility of the services provided by the company, so it always makes JNE the first choice in the shipping and receiving services of goods. Fourth, the goal of MMT is implemented effectively. Along with the demand for service needs, the company carries out HR development through recruitment of competent staff and includes employees in technical training and training, adds a fleet of transportation facilities for sending and receiving goods, and updates the internet needs. The goal of MMT is achieved to the maximum. Fifth, real changes from MMT are carried out effectively. The community is easy to access JNE services located in downtown Gorontalo, handled well at affordable costs. Gorontalo Main Branch JNE service meets the expectations and expectations of the customer community. This study concluded that Integrated Quality Management (MMT) at JNE Main Branch of Gorontalo is carried out effectively. Keywords: Effectiveness, Integrated Management Quality.